Content Inc. how entrepreneurs use content to build massive audiences and create radically successful businesses - Pulizzi, Joe, author (McGraw-Hill Education, 2016)
"A pioneer of content marketing, Joe Pulizzi has cracked the code when it comes to the power of content in a world where marketers still hold fast to traditional models that no longer work. In Content Inc., he breaks down the business-startup process into six steps, making it simple for you to visualize, launch, and monetize your own business...This model has worked wonders for Pulizzi and countless other people featured in the book. Connect these six pieces like a puzzle, and before you know it, you'll be running your own profitable, scalable business. Pulizzi walks you step-by-step through the process, based on his own success (and failures) and real-world multimillion-dollar examples from multiple industries and countries. Whether you're seeking to start a brand-new business or drive innovation in an existing one, Content Inc. provides everything you need to reverse engineer the traditional entrepreneurial model for better, more sustainable success." -- Book jacket